"Only those who like flour are those who know how to sift": Possibility of developing the associated production in the Farinheiras of the Carlos Marighella settlement in Poxoréu/MT - Monlevade, Ana Paula Bistaffa de; Ribeiro, Marcela de Almeida Silva; Siqueira, Sandra Maria de Oliveira (Seven Editora, 2023)
The present study aimed to present the associated production as a possibility of collective performance of the families, in the production of cassava flour - currently produced in an individualized way - of the Carlos Marighella settlement in the municipality of Poxoréu/MT, with a view to adding value in the food production process, facing the market that has become scarce, due to the advancement of the Brazilian economic recession. By launching the gaze on the Mato Grosso territory we refer to the historical process that has set up the existing land structure today, In which this settlement, as well as the families belonging to it, are experiencing today. With this, there is a search for alternatives of survival, on the part of the settlers. Thus, it is presented as resistance to the current conjuncture that, individually, will direct them to the deepening of the precarization of work. Thus, the proposal for this study presented, points to a positive alternative, collectively creating a new form of survival and mutual help, without necessarily relying on state support. DOI:https://doi.org/10.56238/interdiinovationscrese-034